Meningkatkan Hasil Belajar PAKBP dengan Model PBL Materi Perempuan dan Laki-Laki Diciptakan sebagai Citra Allah Melalui Metode Dinamika Kelompok Fase C Kelas V SDN Mangkubumen Kidul Surakarta - Yohanes Pratamto Henri (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Catholic Religious Education at SDN Mangkubumen Kidul Surakarta City is carried out with an Independent curriculum. As is known, the learning method is a means of interaction between teachers and students in learning activities towards the objectives, types, and learning materials as well as the teacher's ability to understand and implement the method. In this study, the researcher chose the Group Dynamics learning method to solve the existing problem, namely trying to research whether the use of Group Dynamics learning can improve student learning outcomes carried out by classroom action research. The title of this study is "IMPROVING PAKBP LEARNING OUTCOMES WITH THE PBL MODEL OF WOMEN AND MEN MATERIAL CREATED AS THE IMAGE OF ALLAH THROUGH THE PHASE C GROUP DYNAMICS METHOD CLASS V SDN MANGKUBUMEN KIDUL SURAKARTA." The type of research conducted by the researcher is Classroom Action Research, which is a form of reflective study by actors who take action to improve students' entrepreneurial attitudes. According to Arikunto (2002:91), classroom action research is a scrutiny of activities that are deliberately raised, and occur in a classroom. Wardani (2001: 1.4) defines classroom action research as research conducted by teachers in their own classrooms through self-reflection, with the aim of improving their performance as teachers, so that student learning outcomes increase. In this study, the researcher used the PTK model of Kemmis and Mc Taggart. Based on the description of the study and the results of the study, it can be said that the average learning outcome of Class V students of PAKPP SDN Mangkubumen Kidul Surakarta City from cycle I to cycle II has increased, namely the increase in the average class score from cycle I to cycle II increased by 12.5%, from 80.75 to 93.25. The achievement of the implementation of the learning process in accordance with the action scenario increased by 5% from 95% to 100%. The process of group dynamics became better from cycle I to cycle II increased by 33.5% from 66.5% to 100% So it can be concluded that there is an increase in the learning outcomes of PAKBP grade V students with the PBL model of the material Women and Men Created as the Image of Allah.